PM2.5-bound polycyclic aromatic hydrocarbons (PAHs) and nitrated PAHs (NPAHs) in rural and suburban areas in Shandong and Henan Provinces during the 2016 Chinese New Year's holiday. (July 2019) - Zhang, Junmei; Yang, Lingxiao; Ledoux, Frédéric; Courcot, Dominique; Mellouki, Abdelwahid; Gao, Ying; Jiang, Pan; Li, Yanyan; Wang, Wenxing
Abstract: Eighteen polycyclic aromatic hydrocarbons (PAHs) and fourteen nitrated PAHs (NPAHs) in PM2.5 samples were collected during the 2016 Chinese New Year's holiday (CNY) at one suburban and three rural sites in Shandong and Henan Provinces. The PAH and NPAH concentrations were highest at the suburban site. The rural PAH concentrations in Qingzhou (QZ), Heze (HZ), and Liaocheng (LC) were higher than those measured at many other urban sites, indicating that PAHs pollution was notably higher in the suburban and rural sites during this festive period. Elevated PAH concentrations were observed during fireworks periods, but fireworks burning was not a significant or direct PAHs or NPAHs source based on molecular profiles and diagnostic ratios. The measured PAHs and NPAHs at the sampling sites mainly originated from coal and biomass burning. The increased concentrations during CNY's Eve may be related to behavioural changes during the period. Secondary formation of NPAHs mainly occurred via OH radical chemistry at all four sites. Fireworks burning did not increase secondary formation of NPAHs. ∑BaPeq concentrations exhibited strong correlations with PAHs concentrations, and the highest and lowest concentrations were observed in QZ and Xiping (XP), respectively. The incremental lifetime cancer risk (ILCR) was calculated to be between 10 −6 and 10 −4 for 1–70 years old persons, with the highest risks observed in the adult (30–70 years) and the toddler (1–6 years) groups. Graphical abstract: Image 1 Highlights: Increase of PAHs levels during Chinese New Year's Eve. Coal/biomass burning were the main sources of PAHs and NPAHs. Fireworks could not promote the secondary formation of NPAHs. Relatively high potential risk for cancer existed for the adult and toddler groups. Abstract : Fireworks would not appear to be an important and direct source of PAHs and NPAHs, and fireworks could not increase the contribution of secondary formation of NPAHs.